Significados la muerte e inmigración en la película Biutiful - Petrescu, Olivia Narcisa (Acta Hispanica, 2015)
Starting from the hermeneutics of the plot identifiable in the movie Biutiful, directed by the Mexican Alejandro González Iñárritu in 2010, our study aims to analyse the multicultural connections among the characters, in terms of their tragic destinies, of the death, illegal immigration and poverty in an unusual framework as it is that of a sordid and marginal Barcelona.Even if the story concerns only a film, one could embody multiple intertextual references which allude to fantasy literature. Besides, the harsh reality and the anxieties experienced by the main protagonist establish a credible insight of some real ethnic, social and spiritual phenomena, specific for XXI century Europe, but also universal for all ages of humanity. From this perspective, our exegesis is meant to be a cultural interpretation of the life-death significance, as perceived through three crisscrossing communities in the motion picture: the Spanish, Chinese, and Senegalese communities, which metaphorically represent three very different continents and cultures.